(untitled) (Journal of the College of Basic Education, 2024)
The Palestinian issue was of great importance to the Arab countries in general and the Emirate of Transjordan in particular, due to the geographical extension and interconnectedness between the Jordanian and Palestinian peoples, as this region represented a single geographical spot during the Ottoman era, and was then divided between the colonial countries. By virtue of this, Prince Abdullah had specific positions and views different from the rest of the Arab countries regarding the Palestinian issue and the issue of dividing Palestine between the Arabs and the Zionists, as he had an old desire to annex the lands of Syria and Palestine within what was known as “Greater Syria.” The research shed light on the Jordanian position through two axes: the first axis dealt with the formation of the Royal Commission (Peel Commission) and the Jordanian position on it, while the second axis touched on the committee’s report and the Jordanian position on it.